Water purification by means of membranes in the city of Pampas -Tayacaja - Gutierrez Collao, Jairo Edson (2023)
At present, environmental requirements and the growth of environmental management systems, have generated a change of consciousness at an industrial level, leading this to satisfy the expectations of customers both in the quality of products or services, as well as in the ways environmentally friendly production facilities, the above added to environmental regulations, have generated a change in the production culture in which the enormous losses of raw materials that are discarded into the sewers must be recovered and reincorporated into the production process, resulting in in economic and environmental benefits. In the city of Pampas Tayacaja there is a very latent problem which is the lack of water treatment, which is why most of the population often uses contaminated water in their food thus causing some diseases. For this reason, in this present work an investigation will be proposed on the use of membranes that is certainly suitable today for water treatment. In general, the efficiency of a membrane depends of the composition of the liquid fluid to be treated, other related factors with its maintenance are hydraulic pressure and fouling what is as a result of research, the cleaning of the membranes is key for the issue of treatment costs and efficiency. In conclusion, the technology of the membranes improves water quality and its efficiency influences the maintenance costs.